Proof of principle of helium-beam radiography using silicon pixel detectors for energy deposition measurement, identification, and tracking of single ions - Gehrke, Tim; Jäkel, Oliver; Martišíková, Mária (Medical physics, 2018)
Purpose Hadron therapy has the capability to provide a high dose conformation to tumor regions. However, it requires an accurate target positioning. Thus, the precise monitoring of the patient's anatomical positioning during treatment is desirable. For this purpose, hadron-beam radiography with protons (pRad) and ions (iRad) could be an attractive tool complementing the conventional imaging technologies. On the pathway to an envisaged clinical application, several challenges have to be addressed. Among them are achieving the desired spatial resolution in the presence of multiple Coulomb scattering (MCS), performing radiographs with a sufficient thickness resolution at clinically applicable dose levels, and the search for combinations of particularly suitable hadrons and detectors. These topics are investigated in this work for a detection system based on silicon pixel detectors. Methods A method of iRad based on energy deposition measurements in thin layers is introduced. It exploits a detection system consisting of three parallel silicon pixel detectors, which also enables particle tracking and identification. Helium ions, which exhibit less pronounced MCS than protons, were chosen as imaging radiation. A PMMA phantom with a mean water-equivalent thickness (WET) of 192 mm, containing maximal WET-variations of ±6 mm, was imaged with a 173 MeV/u helium ion beam at the Heidelberg Ion-Beam Therapy Center. WET-differences in form of 2.3 mm × 2.3 mm steps were aimed to be visualized and resolved in images of the energy deposition measured behind the phantom. The detection system was placed downstream of the imaged object in order to detect single ions leaving it. The combination of the measured information on energy deposition, ion type, and the track behind the phantom was used for the image formation, employing a self-developed data-processing procedure. Results It was shown that helium-beam radiography is feasible with the reported detection system. The introduced data preprocessing purified the detector signal from detector artifacts and improved the image quality. Additionally, the rejection of hydrogen ions originating from nuclear interactions was shown to increase the contrast-to-noise ratio (CNR) by at least a factor of 2.5. This enabled the resolution of relative thickness differences of 1.2% at a dose level typical for diagnostic x-ray images. The spatial resolution was improved by taking into account the direction of single helium ions leaving the phantom. A spatial resolution (MTF10%) of at least 1.15p mm−1 for the presented experimental set-up was achieved. Conclusion A successful feasibility study of helium-beam radiography with the introduced detection system was conducted. The methodology of iRad was based on energy deposition measurements in thin silicon layers. The tracking of single ions and the method of the ion identification was shown to be important for helium-beam radiography in terms of spatial resolution and CNR.